Model Pembelajaran Problem Based Learning untuk Meningkatan Hasil dan Aktivitas Belajar Matematika Siswa SMK - Novita Syahputri; Nurdalilah Nurdalilah; Desniarti Desniarti; Wilda Hasanah; Pesta Rut Cahaya Sitanggang (Journal on Education, 2024)
The low results and activities in mathematics learning are the main basis for this research. The aim of this research is to see how well the Problem Based Learning (PBL) model can improve students' mathematics learning outcomes and activities. The research was carried out at SMK Negeri 7 Medan. This research uses Classroom Action Research (PTK). The respondents of this research were class X AKL 3 students at SMK Negeri 7 Medan, consisting of 35 people. Data collection techniques use observation and test techniques. Data collection instruments used observation sheets and essay tests. The research results showed that student activity in cycle I was 70% (good) and in cycle II it was 90% (very good). Then the students' classical learning results in cycle I were 57.14% (Medium) with an average of 76.36 and in cycle II it was 88.57% (Very high) with an average of 87.71. So the conclusion of this research is that through the application of the Problem Based Learning (PBL) learning model, it can improve students' mathematics learning outcomes and activities in statistics material in class X AKL 3 SMK Negeri 7 Medan.